Polymer supported vanadium and molybdenum complexes as potential catalysts for the oxidation and oxidative bromination of organic substrates - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (Dalton Transactions, 2006)
{The Schiff base (H(2)fsal-ohyba) derived from 3-formylsalicylic acid and o-hydroxybenzylamine has been covalently bonded to chloromethylated polystyrene cross-linked with 5% divinylbenzene ( abbreviated as PS-H(2)fsal-ohyba, I). Treatment of [
Keywords: Bile acids; bis-steroids; hybrids; Peptides; polyamines; saponins; steroidal conjugates; synthetic ionophores